Analyzing the Effect of Perceived Organizational Support on Organizational Citizenship Behavior with the Mediating Role of Organizational Indifference - Vahid Bekhradi Nasab; Milad Ahmadi (مدیریت نوآوری و راهبردهای عملیاتی, 2022)
Purpose: Nowadays, due to the increasing complexity, the issue of perceived organizational support and the need for organizational citizen behaviour has been considered more, while the topic of organizational indifference is one of the factors that can compromise the competitive position of the organization. Therefore, it is essential to consider it. This research investigates the relationship between perceived organizational support and organizational citizenship behaviour through the role of organizational indifference as a mediation.Methodology: This research is practical in terms of purpose and is descriptive-survey and correlation type in terms of nature. The statistical population is established of employees of Isfahan Steel Tehnika Co. A library method, such as books and scientific articles, was used to collect information on the subject literature, and for measuring the model's variables, a standard, valid, and reliable questionnaire was used. The sampling method is randomized. For analyzing the data to test research hypotheses, we used inferential statistics and test structural equations in SPSS 22 and Smart Pls 2.0 software.Findings: The findings indicate that perceived organizational support is influential and effective on organizational citizenship behaviour and its dimensions. Also, perceived organizational support indirectly affects organizational citizenship behaviour through the role of organizational indifference as a mediator.Originality/Value: Analyzing the effect of perceived organizational support on organizational citizenship behaviour by emphasizing the mediating role of organizational indifference is an essential tool for translating employees' voices and considering their wants and needs, which was used for the first time in this study.